Current and emerging treatment options for autoimmune hemolytic anemia. (3rd October 2018) - Barcellini, Wilma; Fattizzo, Bruno; Zaninoni, Anna
ABSTRACT: Introduction : Autoimmune hemolytic anemia (AIHA) is a heterogeneous disease mainly due to autoantibody-mediated destruction of erythrocytes but also involves complement activation, dysregulation of cellular and innate immunity, and defective bone marrow compensatory response. Several drugs targeting these mechanisms are under development in addition to standard therapies. Areas covered : The following targeted therapies are illustrated: drugs acting on CD20 (rituximab, alone or in association with bendamustine and fludarabine) and CD52 (alemtuzumab), B cell receptor and proteasome inhibitors (ibrutinib, bortezomib), complement inhibitors (eculizumab, BIVV009, APL-2), and other drugs targeting T lymphocytes (subcutaneous IL-2, belimumab, and mTOR inhibitors), IgG driven extravascular hemolysis (fostamatinib), and bone marrow activity (luspatercept). Expert opinion : Although AIHA is considered benign and often easy to treat, chronic/refractory cases represent a challenge even for experts in the field. Bone marrow biopsy is fundamental to assess one of the main mechanisms contributing to AIHA severity, i.e. inadequate compensation, along with lymphoid infiltrate, the presence of fibrosis or dyserythropoiesis. The latter may give hints for targeted therapies (either B or T cell directed) and for new immunomodulatory drugs. Future studies on the genomic landscape in AIHA will further help in designing the best choice, sequence and/or combination of targeted therapies.